Thrombin Induces COX-2 and PGE2 Expression via PAR1/PKCalpha/MAPK-Dependent NF-kappaB Activation in Human Tracheal Smooth Muscle Cells - Yang, Chien-Chung; Hsiao, Li-Der; Shih, Ya-Fang; Hsu, Chih-Kai; Hu, Chia-Yu; Yang, Chuen-Mao (Mediators of Inflammation, 2022)
The inflammation of the airway and lung could be triggered by upregulation cyclooxygenase (COX)-2 and prostaglandin E2 (PGE2) induced by various proinflammatory factors. COX-2 induction by thrombin has been shown to play a vital role in various inflammatory diseases. However, in human tracheal smooth muscle cells (HTSMCs), how thrombin enhanced the levels of COX-2/PGE2 is not completely characterized. Thus, in this study, the levels of COX-2 expression and PGE2 synthesis induced by thrombin were determined by Western blot, promoter-reporter assay, real-time PCR, and ELISA kit. The various signaling components involved in the thrombin-mediated responses were differentiated by transfection with siRNAs and selective pharmacological inhibitors. The role of NF-κB was assessed by a chromatin immunoprecipitation (ChIP) assay, immunofluorescent staining, as well as Western blot. Our results verified that thrombin markedly triggered PGE2 secretion via COX-2 upregulation which were diminished by the inhibitor of thrombin (PPACK), PAR1 (SCH79797), Gi/o protein (GPA2), Gq protein (GPA2A), PKCα (Gö6976), p38 MAPK (SB202190), JNK1/2 (SP600125), MEK1/2 (U0126), or NF-κB (helenalin) and transfection with siRNA of PAR1, Gqα, Giα, PKCα, JNK2, p38, p42, or p65. Moreover, thrombin induced PAR1-dependent PKCα phosphorylation in HTSMCs. We also observed that thrombin induced p38 MAPK, JNK1/2, and p42/p44 MAPK activation through a PAR1/PKCα pathway. Thrombin promoted phosphorylation of NF-κB p65, leading to nuclear translocation and binding to the COX-2 promoter element to enhance promoter activity, which was reduced by Gö6976, SP600125, SB202190, or U0126. These findings supported that COX-2/PGE2 expression triggered by thrombin was engaged in PAR1/Gq or Gi/o/PKCα/MAPK-dependent NF-κB activation in HTSMCs.